Hu Shi's Model of Rhetorical Pragmatic Argumentation. Issue 2 (4th May 2019) - Butterfield, Rya
ABSTRACT: During China's Republican Period, scholar and reformer Hu Shi advanced a rhetorical pragmatic project for democratic reform. In this essay, I argue that the dissertation Hu wrote under the advisement of John Dewey, "The Development of Logical Method in Ancient China, " was itself a groundbreaking piece of rhetorical invention that functioned as part of Hu's project by reinterpreting ancient Chinese classics as the foundations for a model of rhetorical pragmatic argumentation.